Socially responsible plastic : is this possible? - Crowther, David; Quoquab, Farzana, 1978- (Emerald Publishing Limited, 2023)
Plastics have long been considered useful, providing such economic advantages as reduced cost and social benefits like increased hygiene and the preservation of food. However, plastic products have greatly contributed to climate change. Half of all plastic produced is single use. The discarded plastics are dumped into landfills and find their way into bodies of water, causing serious environmental pollution and health hazards. Addressing this paradoxical situation, Socially Responsible Plastic answers the question: can using plastic ever be socially responsible? While humanity is threatened by the environmental pollution caused by plastic, some countries are implementing and accepting environmentally friendly behaviour, while others are still falling behind. More specifically, adopting environmentally friendly behaviour is still in its infancy in developing nations. The authors look at socially responsible plastic in countries ranging from China, Malaysia, Pakistan, Spain, Australia and India to Sri Lanka, Nigeria and Bangladesh, with research covering tourism, waste management, the food and drink industry, and the possible advantages of responsible plastic use. Developments in Corporate Governance and Responsibility offers the latest research on topical issues by international experts and has practical relevance to business managers.
Keywords: Plastics -- Environmental aspects.; Plastic scrap.; Business & Economics -- Environmental Economics.; Plastics & polymers technology.; elektronické knihy; electronic books